Dissemination of agricultural technology as an innovation for modern agricultural transformation in Lebak Village, Grabag - Adiana, Beta Estri; Laili, Muhammad Akmal Nisfa; Ramadhan, Aditya Wahyu; Fisabilillah, Safira Nisa; Fatikasari, Amelia; Najwa, Amanda Fitria; Malinda, Indah Putri; Fakhruriza, Fakhruriza; Rahmatillah, Putri Kaifa; Alkautsar, Zidane Ilman; Prasetiyo, Agung (Community Empowerment, 2025)
Agriculture is a vital sector that plays a role in fulfilling food needs, economic development, and community welfare, particularly in rural areas. However, most farmers in Lebak Village, Grabag District, Magelang Regency, still rely on conventional methods that are inefficient and do not yet utilize modern agricultural technology. This community service activity aims to enhance farmers' understanding and skills related to appropriate technology, specifically a sensor-based automatic soil moisture irrigation system, a portable soil pH meter, and a circle model seed planting pattern. The method employed in this activity was the socialization of appropriate technology. The results show a significant improvement, with the average understanding score increasing by 91%, 85% of farmers being able to operate the pH meter, water use efficiency rising by 28%, and corn planting time becoming 44% faster. These outcomes prove that participatory socialization based on direct practice is effective in boosting farmers' capacity, both cognitively and technically. This activity is expected to serve as a model for strengthening the adoption of modern agriculture based on adaptive, productive, and sustainable precision technology at the village level.